How can we possibly resolve the planet's nitrogen dilemma?. Issue 1 (15th November 2022) - Matassa, Silvio; Boeckx, Pascal; Boere, Jos; Erisman, Jan Willem; Guo, Miao; Manzo, Raffaele; Meerburg, Francis; Papirio, Stefano; Pikaar, Ilje; Rabaey, Korneel; Rousseau, Diederik; Schnoor, Jerald; et al.
Abstract: Nitrogen is the most crucial element in the production of nutritious feeds and foods. The production of reactive nitrogen by means of fossil fuel has thus far been able to guarantee the protein supply for the world population. Yet, the production and massive use of fertilizer nitrogen constitute a major threat in terms of environmental health and sustainability. It is crucial to promote consumer acceptance and awareness towards proteins produced by highly effective microorganisms, and their potential to replace proteins obtained with poor nitrogen efficiencies from plants and animals. The fact that reactive fertilizer nitrogen, produced by the Haber Bosch process, consumes a significant amount of fossil fuel worldwide is of concern. Moreover, recently, the prices of fossil fuels have increased the cost of reactive nitrogen by a factor of 3 to 5 times, while international policies are fostering the transition towards a more sustainable agro‐ecology by reducing mineral fertilizers inputs and increasing organic farming. The combination of these pressures and challenges opens opportunities to use the reactive nitrogen nutrient more carefully. Time has come to effectively recover used nitrogen from secondary resources and to upgrade it to a legal status of fertilizer. Organic nitrogen is a slow‐release fertilizer, it has a factor of 2.5 or higher economic value per unit nitrogen as fertilizer and thus adequate technologies to produce it, for instance by implementing photobiological processes, are promising. Finally, it appears wise to start the integration in our overall feed and food supply chains of the exceptional potential of biological nitrogen fixation. Nitrogen produced by the nitrogenase enzyme, either in the soil or in novel biotechnology reactor systems, deserves to have a 'renaissance' in the context of planetary governance in general and the increasing number of people who desire to be fed in a sustainable way in particular. Abstract : Nitrogen is the most crucial element in the production of nutritious feeds and foods, yet, the production and massive use of fertilizer nitrogen constitutes a major threat in terms of environmental health and sustainability. Time has come to implement a more sustainable and circular management of nitrogen by recovering used nitrogen from secondary resources and by leveraging the exceptional potential of biological nitrogen fixation.